Motorized Recreation Sounds Influence Nature Scene Evaluations: The Role of Attitude Moderators - Benfield, Jacob; Taff, B. D.; Weinzimmer, David; Newman, Peter (Frontiers in Psychology, 2018)
Soundscape assessment takes many forms, including letting the consequences of the soundscape be an indicator of soundscape quality or value. As a result, much social science research has been conducted to better quantify problem soundscapes and the subsequent effects on humans exposed to them. Visual evaluations of natural environments are one area where research has consistently shown detrimental effects of noisy or anthropogenic soundscapes (e.g., those containing noise from motorized recreation), but the potential moderating role of individual attitudes toward elements within the soundscape has not been sufficiently explored. This study demonstrates that both pro-motorized recreation and pro-motorized recreation management attitudes can alter the effect of motorized recreation noise on scenic evaluations in opposing directions. Pro-recreation attitudes lessen the effect of the soundscape, while pro-management attitudes heighten the negative effect of anthropogenic sounds on scenic evaluation. The implications for other areas of soundscape research, especially with regard to soundscape quality assessment through experienced outcomes, are discussed, including possible strategies for prioritizing known or relevant moderating variables.